Persistent mRNA and miRNA expression changes in irradiated baboons. Issue 1 (December 2018) - Port, Matthias; Hérodin, Francis; Valente, Marco; Drouet, Michel; Ostheim, Patrick; Majewski, Matthäus; Abend, Michael
Abstract We examined the transcriptome/post-transcriptome for persistent gene expression changes after radiation exposure in a baboon model. Eighteen baboons were irradiated with a whole body equivalent dose of 2.5 or 5 Gy. Blood samples were taken before, 7, 28 and 75–106 days after radiation exposure. Stage I was a whole genome screening for mRNA combined with a qRT-PCR platform for detection of 667 miRNAs. Candidate mRNAs and miRNAs differentially up- or down-regulated in stage I were chosen for validation in stage II using the remaining samples. Only 12 of 32 candidate genes provided analyzable results with two mRNAs showing significant 3–5-fold differences in gene expression over the reference (p < 0.0001). From 667 candidate miRNAs, 290 miRNA were eligible for analysis with 21 miRNAs independently validated using qRT-PCR. These miRNAs showed persistent expression changes on each day and over days 7–106 days after exposure (n = 7). In particular miR-212 involved in radiosensitivity and immune modulation appeared persistently and 48–77-fold up-regulated over the entire time period. We are finally trying to put our results into a context of clinical implications and provide possible hints on underlying molecular mechanisms to be examined in future studies.